2016
DOI: 10.24319/jtpk.6.149-158
|View full text |Cite
|
Sign up to set email alerts
|

Pola Pemanfaatan Daerah Penangkapan Ikan Untuk Mereduksi Konflik Perikanan Tangkap Di Perairan Utara Aceh

Abstract: Conflicts in fisheries sector started especially a few years ago between local and multi-national fishing companies in Northen Aceh waters. This conflicts occur because unfair exploitation of fish resources have limited, so it make the challenging of fishing ground. This study was aimed to analyze causing factors and the effects of conflicts in the fisheries sector and how to reduce the conflicts. Analyze methods of this research use descriptive and AHP (Analytical Hierarchy Process). Results showed that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…Cahaya lampu dari bagan perahu menarik ikan-ikan yang tadinya berada di dalam rumpon, akibatnya pejala rumpon dirugikan. Tetapi, bagi nelayan nonrumpon, rumpon dianggap merugikan karena menghalangi migrasi ikan (Purnama, Simbolon, & Mustaruddin, 2015). Alat tangkap dogol menimbulkan banyak konflik di banyak tempat (Satria).…”
Section: Pembahasan Potensi Konflik Dan Pembagian Zona Tangkapunclassified
See 1 more Smart Citation
“…Cahaya lampu dari bagan perahu menarik ikan-ikan yang tadinya berada di dalam rumpon, akibatnya pejala rumpon dirugikan. Tetapi, bagi nelayan nonrumpon, rumpon dianggap merugikan karena menghalangi migrasi ikan (Purnama, Simbolon, & Mustaruddin, 2015). Alat tangkap dogol menimbulkan banyak konflik di banyak tempat (Satria).…”
Section: Pembahasan Potensi Konflik Dan Pembagian Zona Tangkapunclassified
“…Penggunaan trawl dilarang oleh pemerintah karena sifatnya yang destruktif. Pengoperasian trawl dapat merusak rumpon (Purnama et al, 2015). Dengan wilayah yang relatif sempit akibat perubahan fishing ground menjadi area konservasi terumbu karang atau perubahan fishing ground menjadi jalur pipa gas (Marliza, 2022), pemerintah bersama nelayan berusaha semaksimal mungkin memanfaatkan zona yang telah ditetapkan sebagai area penangkapan ikan, misalnya; untuk trammel net atau jaring gondrong di kedalaman 7-10 meter, Bagan tancap di kedalaman 9-20 meter.…”
Section: Pembahasan Potensi Konflik Dan Pembagian Zona Tangkapunclassified
“…The results leverage of the social domain showed that the metrics most important to the domain's sustainability index value are fishing patterns and sand mining (Figure 7). Fishing practices that some fishermen already kill in the future cause social tension due to the use of the same resources (Purnama et al, 2015, Lorenzo et al, 2019. As an example, Zulkifli et al (2019) stated that the degree of fisheries conflict in Kalimantan was triggered by 42% conflict over resource usage, 38% conflict over resource use, and 20% conflict over conflict resource use.…”
Section: Attributementioning
confidence: 99%
“…Harm to coral reef habitats from destructive fishing practices will cause potential social problems. Due to discrepancies in fishing gear on the same estate, these social issues can cause social tensions (Purnama et al, 2015;Lorenzo et al, 2019). Thus, a model of sustainable management of coral reefs is required.…”
Section: Introductionmentioning
confidence: 99%
“…Perebutan sumber daya ikan yang memanfaatkan perairan pesisir Kabupaten Tangerang sering mengakibatkan konflik antar nelayan. Dampak yang dihasilkan dari konflik perikanan tangkap adalah terganggunya habitat sumber daya ikan, menurunnya hasil tangkapan dan pendapatan nelayan tradisional (Purnama et al, 2015). Menurut Dwiyanto (2017), penyelesaian konflik perebutan DPI tidak dapat diselesaikan sesama nelayan, harus ada peran aktif kepolisian dan kementerian kelautan dan perikanan (KKP).…”
Section: Bahasanunclassified